Effectiveness of low to moderate Thai exercise training on lipid profiles and physical performance in overweight Thai people: a randomised controlled trial - Sawangwong, Pornchai; Tungsukruthai, Sucharat; Nootim, Preecha; Sriyakul, Kusuma; Kumar Pawa, Kammal; Tungsukruthai, Parunkul; Phetkate, Pratya (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. This study investigated the effect of low to moderate Thai exercise training (Ruesi Dadton) compared to standard self-care on lipid profiles and physical performance in overweight individuals.Methods. Sixty-one participants were randomly assigned to either an intervention group, which practised Ruesi Dadton exercises for 60 minutes, three times per week for 12 weeks under the supervision of a Thai Traditional Medicine (TTM) Practitioner via an online platform, or a control group, which received guidance on self-care for managing hyperlipidaemia.Results. The intervention group demonstrated a decreasing trend in total cholesterol (TC) and a significant reduction in LDL cholesterol (LDL) levels, from 141.52 ± 32.29 to 125.68 ± 26.74 mg/dL (p < 0.05). In contrast, LDL levels increased in the control group (p < 0.05). Additionally, the intervention group showed improvements in physical performance (p < 0.05) and anthropometric indices (p < 0.05), while the control group experienced a decrease in these outcomes. Regarding quality of life, both groups showed significant improvement (p < 0.05).Conclusions. It could be concluded that low to moderate Ruesi Dadton effectively manages and reduces blood lipid levels and positively impacts physical performance, anthropometric indices, and quality of life.
Keywords: quality of life; lipid profile; dyslipidaemia; physical performance; anthropometric indices; Thai exercise training